Governing by the people: the example of California’s propositions (1990-2012) - Anne DEBRAY (Cahiers du MIMMOC)
American state Constitutions provide for direct democracy in which citizens are given the tools to impact their government. The most common way is via the proposition which can change the state law. This paper focuses on two controversial sets of propositions from California in the recent past: medical and recreational marijuana, and same-sex marriage. It questions the different powers at play such as money, special interests, and the potential institutional checks. Are propositions the expression of public opinion? How effective are these examples of direct democracy?